Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Said, Madhukar S.; Udavant, Rohini; Sahu, Amit Kumar; Khan, Abujunaid; Nayak, Rashmi; Dastager, Syed G.; Kumar, Pradeep; Gajbhiye, Jayant (Natural Product Research, 2020)
The first total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate (butenolide cinnamate) was achieved using commercially available starting material. The synthesized compound was found to have promising antibacterial activity against Gram-negative strainsEscherichia coli(ATCC 8739),Salmonella typhimurium(ATCC 23564) andPseudomonas aeruginosa(ATCC 19154) with a minimum inhibitory concentration of 2.0 mu g/mL, 1.0 mu g/mL and 2.0 mu g/mL, respectively. Notably, the compound was more potent against Gram-negative test strains than the Gram-positive test strains.
Keywords: antibacterial activity; butenolide cinnamate; Total synthesis

Tuning phosphorescence features of triphenylamines by varying functional groups and intermolecular interactions - Goudappagouda; Asokan, Kiran; Nayak, Rashmi; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Dyes and Pigments, 2020)
Organic room temperature phosphorescent materials are known for their synthetic feasibility, tunable phosphorescence wavelength and lifetime, etc. Hence new design strategies have been applied on various fluorophores to improve phosphorescence features. Among those, triphenylamines are phosphorescence active due to the presence of nitrogen atom, propeller molecular structure, and intermolecular interactions in the crystal state. Here we have studied the room temperature phosphorescence of a series of triphenylamines with various functional groups. Detailed studies have shown that the phosphorescence can be fine-tuned by functional group modification. A long phosphorescence lifetime around 100 ms at room temperature in air can be achieved by the interplay of intermolecular interactions, singlet-triplet energy gap and extent of intersystem crossing using functional group variation. Interestingly, an exciplex assisted ultralong phosphorescence lifetime (more than 20 times) is observed for a combination of triphenylamine and naphthalenemonoimide in air.
Keywords: Exciplex; fluorescence; Phosphorescence; triphenylamine